2016
DOI: 10.1017/jpr.2016.49
|View full text |Cite
|
Sign up to set email alerts
|

The dominating colour of an infinite Pólya urn model

Abstract: ABSTRACT. We study a Pólya-type urn model defined as follows. Start at time 0 with a single ball of some colour. Then, at each time n ≥ 1, choose a ball from the urn uniformly at random. With probability 1/2 < p < 1, return the ball to the urn along with another ball of the same colour. With probability 1 − p, recolour the ball to a new colour and then return it to the urn. This is equivalent to the supercritical case of a random graph model studied by Backhausz and Móri [4,5] and Thörnblad [17]. We prove that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The modification of the classical Ehrenfest urn model [41,44] that we analyze was originally introduced in [38] to understand billiard dynamics comprising a Maxwell demon [45][46][47], and is embedded in a long history of urn models studied in statistical mechanics [48][49][50][51][52][53][54][55][56][57][58][59]. It refers to N particles initially distributed inside two urns.…”
Section: The Urn Modelmentioning
confidence: 99%
“…The modification of the classical Ehrenfest urn model [41,44] that we analyze was originally introduced in [38] to understand billiard dynamics comprising a Maxwell demon [45][46][47], and is embedded in a long history of urn models studied in statistical mechanics [48][49][50][51][52][53][54][55][56][57][58][59]. It refers to N particles initially distributed inside two urns.…”
Section: The Urn Modelmentioning
confidence: 99%
“…If X(t) is constructed correctly, then the laws of {X i } i∈N and {X(τ i )} i∈N are equal in distribution. Using a construction for an embedding from [62], we are able get an explicit distribution for π stake (h) i under the assumptions of this section.…”
Section: −Pimentioning
confidence: 99%
“…This follows directly from [62, Lemma 2.1], once we map the setup of §3 to their problem. In [62], one constructs a Pólya urn such that if a ball of color c is chosen, then in their notation, with probability p lemma , Algorithm 7 update markowitz(µ prev , π stake , π lend , , γ t , λ)…”
Section: A Notationmentioning
confidence: 99%
See 1 more Smart Citation
“…He introduced a new type of urn scheme [22], where at each step with some positive probability a new color can be introduced. Several authors studied this slightly different model in the context of the Griffiths-Engen-McCloskey (GEM) model, the Poisson-Dirichlet distribution, and the Ewens sampling formula [13,20,21,38]. It was also observed that Hoppe's urn scheme has a deep relation with certain combinatorial stochastic processes, known as the Chinese restaurant process [1,34].…”
Section: Introductionmentioning
confidence: 99%